2022
DOI: 10.1590/s1517-707620220002.1382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyurethane ratio on mechanical behavior of banana fiber/polyurethane-vinylester matrix composites

Abstract: A customary ratio of vinyl ester (VER) and Polyurethane (PU) resin were chosen as the matrix material (blend) to attain the complete Interpenetrating Polymer Networks (IPN). In this course of research, the mechanical properties of the Banana fiber reinforced IPN (blend) matrix were thoroughly investigated by precisely varying the loading of polyurethane into vinylester as 0%, 10%, 20%, 30%, 40%, 50% PU respectively. Besides that, the fabricated banana fiber reinforced polyurethane loaded IPN laminate were expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The flexural properties of a resin system are a measure of the energy absorbed by the material during fracture under static loading 28 . Figure 8ab shows the flexural strength and modulus of C‐PESC3/E51 at different PHR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flexural properties of a resin system are a measure of the energy absorbed by the material during fracture under static loading 28 . Figure 8ab shows the flexural strength and modulus of C‐PESC3/E51 at different PHR.…”
Section: Resultsmentioning
confidence: 99%
“…The flexural properties of a resin system are a measure of the energy absorbed by the material during fracture under static loading. 28 to the increase in crosslink density. The flexural modulus was almost unchanged, which was due to the increase in crosslink density caused by the participation of carboxyl groups in curing, thus maintaining the flexural modulus at a high level.…”
Section: Mechanical Properties Of C-pescmentioning
confidence: 99%
“…9 At present, fiber reinforcement is at the forefront of material research, and its development opens up various possibilities of material modification and enhancing functionality. [10][11][12][13][14][15] Kuram et al compared the mechanical and chemical properties of polypropylene/polyethylene (PP/PE) blends reinforced with glass fibers (GFs) and unreinforced blends and found that the addition of GFs to PP/PE blends is a very effective method to improve their tensile strengths. The tensile strengths of all PP/GF/ PE blends were higher than those of the PP/PE blends.…”
Section: Introductionmentioning
confidence: 99%